Towards Educational Metadata Interoperability on Semantic Web - Behr, André; Primo, Tiago Thompsen; Vicari, Rosa (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2016: Anais do XXVII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2016.1026, 2016)
Metadata is broadly used to describe learning objects and its standards have been developed to improve interoperability. With the current Web extension by the Semantic Web, learning object metadata has been migrating from XML-based metadata formats to semantic metadata formats. This work explores XSLT to provide a solution for this transition of descriptions to educational metadata. The approach consists of retrieve, convert, and store metadata in Semantic Web context. In this work, we converted OBAA metadata in XML to OWL format. The OWL format improved the description semantics and allowed reasoner inference. The converted metadata can be managed by different applications and systems. Along with that, we proposed a strategy to OWL ontology alignment.